OPTIONS FOR DEVELOPMENT OF POWER TRANSMISSIONS OF MOLDAVIAN POWER SYSTEM IN PARALLEL WITH POWER SYSTEM OF UKRAINE - Kalinin L.P.; Zaitsev D.A.; Golub I.V. (Problems of the Regional Energetics, 2012)
The paper focuses on the analysis of possible scenarios for the future development of power transmission of Moldavian Power System in parallel operation with the Power System of Ukraine. In this case the problem is considered in the absence of synchronous connection with ENTSO-E.